Pengaruh Experiential Marketing dan Service Quality terhadap Customer Loyalty: Customer Satisfaction sebagai Variabel Mediasi - Ika Nurul Febrianti; Keni Keni (Jurnal Manajemen Bisnis dan Kewirausahaan, 2021)
The aims of this study are four: first, to explore the effects of experiential marketing and service quality toward customer satisfaction. Second, to explore the effects of experiential marketing and service quality toward customer loyalty. Third, to explore the effects of customer satisfaction toward customer loyalty. Fourth, to find out the effects of experiential marketing and service quality toward customer loyalty if mediated by customer satisfaction. The samples that were collected were 154 respondents who are customers from one of food and beverage industry in Jakarta. The method of data collection is conducted by non-probability sampling with the technique of convenience sampling through online questionnaires. The data were analysed by using PLS-SEM. The results of this research are: First, experiential marketing and service service quality have a positive impact toward customer satisfaction. Second, experiential marketing has a positive impact toward customer loyalty, but service quality does not have a positive impact toward customer loyalty. Third, customer satisfaction has a positive impact toward customer loyalty. Fourth, experiential marketing and service quality have a positive impact toward customer loyalty if mediated by customer satisfaction. Tujuan dari penelitian ini ada empat : pertama menguji pengaruh experiential marketing dan service quality terhadap customer satisfaction. Kedua, menguji pengaruh experiential marketing dan service quality terhadap customer loyalty. Ketiga, menguji pengaruh customer satisfaction terhadap customer loyalty. Keempat, menguji pengaruh experiential marketing dan service quality terhadap customer loyalty bila dimediasi oleh customer satisfaction. Sampel yang dikumpulkan adalah 154 responden yang merupakan konsumen dari salah satu industri makanan dan minuman di Jakarta. Metode pengambilan data adalah non-probability sampling dengan teknik convenience sampling melalui kuesioner online. Analisis data menggunakan PLS-SEM. Hasil penelitian adalah: pertama, experiential marketing dan service quality berpengaruh positif terhadap customer satisfaction. Kedua, experiential marketing berpengaruh positif terhadap customer loyalty tetapi service quality tidak memiliki pengaruh positif terhadap customer loyalty. Ketiga, customer satisfaction memiliki pengaruh positif terhadap customer loyalty. Keempat, experiential marketing dan service quality berpengaruh positif terhadap customer loyalty bila dimediasi oleh customer satisfaction.